Effects of Melatonin and Vitamin C on Smoke Induced Structural Changes in Liver - Çolakoğlu, Neriman; Ozan, Enver; Sönmez, Mehmet Fatih; Yılmaz, Seval; Ozan, Gonca (Fırat University, 2005)
Objectives: This study was undertaken to investigate smoke-induced structural and biochemical changes and protective effects of co-administred of melatonin and vitamin C in the liver. Materials and Methods: Twenty-four Wistar adult female rats were used in this study. Animals were divided into four groups. The first group rats used as control. The second group of rats were inhaleted cigarette. Cigarette inhaleted third and fourth group rats recieved melatonin and vitamin C respectively. End of experimental study liver tissues and blood samples were taken under the ether anesthesia. Tissues were prepared and examined by light microscopy. And biochemicaly, malondialdehyde and glutatyon levels and catalase activity were determined. Results: In the light microscopic observation, sinusoidal dilatation and congestion, mononuclear cell infiltration in some area and karyorectic hepatocytes were detected in the groupe II. In the cigarette inhaleted third and fourth group rats recieved melatonin and vitamin C respectively liver tissues were protected againest smoke relatively. Biochemical examination showed us malondialdehyde and glutatyon levels and catalase activity in the group II higher than group I. While malaondialdehyde levels were decreased by melatonin and vitamin C glutatyon levels were increased. Catalase activity did not change in these groups. Conclusion: As a result, it was determined that cigarette inhalation increased lipid peroxidation and antioxidant system and caused structural changes in the liver. However, it was determined that administration of melatonin and vitamin C provided relative protection against smoke intoxication. ©2005, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Bu çalışmada sigara toksikasyonunun karaciğer dokusunda oluşturduğu yapısal ve biyokimyasal değişiklikler üzerine C vitamini ve melatoninin koruyucu etkilerinin belirlenmesi amaçlandı. Gereç ve Yöntem: Bu çalışmada 24 adet Wistar cinsi ergin dişi sıçan kullanıldı. Sıçanlar 4 gruba ayrıldı. Birinci grup sıçanlar kontrol olarak kullanıldı, ikinci grup sıçanlara sigara inhale ettirildi. Sigara soluyan üçüncü ve dördüncü grup sıçanlara ise her gün sırasıyla melatonin ve C vitamini enjekte edildi. Deney sonunda sıçanlardan eter anestezisi altında karaciğer dokuları ve kan örnekleri alındı. Dokuların bir kısmı rutin histolojik prosedürlerden geçirilerek ışık mikroskobunda incelendi. Bir kısmı ise biyokimyasal tetkiklerle incelendi. Bulgular: Işık mikroskobik incelemelerde ikinci grupdaki sıçanların karaciğer dokularında; sinüzoidlerde dilatasyon ve konjesyon, yer yer mononüklear hücre infiltrasyonu ve karyoreksise giden hepatositler tespit edildi. Sigara ile birlikte uygulanan melatonin ve C vitamininin kısmen koruma sağladığı gözlendi. Yapılan biyokimyasal değerlendirmelerde ikinci gruba ait karaciğer dokularında malondialdehit ve glutatyon düzeyleri ile katalaz aktiviteleri artmış olarak tespit edildi. C vitamini ve melatonin uygulamasının; karaciğer malondialdehit düzeyini anlamlı şekilde düşürdüğü, glutatyon düzeylerini anlamlı bir şekilde artırdığı, katalaz aktivitelerini ise etkilemediği gözlendi. Sonuç: Sigara inhalasyonunun, lipid peroksidasyonunu ve antioksidan sistemi artırdığı, karaciğer dokusunda yer yer yapısal değişiklikler oluşturduğu tespit edildi. Bununla birlikte, C vitamini ve melatonin uygulamasının sigara toksikasyonuna karşı karaciğerde kısmi bir koruma sağladığı belirlendi. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Sigaranın Karaciğerde Oluşturduğu Yapısal Değişiklikler Üzerine Melatonin ve C Vitamininin Etkileri